P-99 Benefits of advance care planning for caregivers of persons with mild dementia of predominantly chinese ethnicity. (1st September 2015) - Ali, N; Anthony, P; Lim, WS; Chong, MS; Poon, EWH; Drury, V; Chan, M
Abstract : Background: Advance care planning (ACP) is a continuous process of conversations, discussions and engagement involving patients, caregivers and healthcare providers. For persons with mild dementia, ACP serves as a window of opportunity for on-going discussions about future health care while still maintaining decisional capacity. Aim: To evaluate the benefits of ACP for caregivers of persons with mild dementia of predominantly Chinese ethnicity. Methods: We recruited 20 English-speaking patient-caregiver dyads, who were predominantly Chinese. Patient-caregiver dyads underwent ACP counselling by a trained ACP facilitator, completed pre-post surveys and participated in post-counselling interviews. We then conducted a concurrent explanatory mixed methods analysis. Results: Prior to ACP counselling, 50% of caregivers had heard of ACP and of these, only half had planned for future care. Post ACP counselling (n = 19), majority found ACP helpful in understanding complications of dementia and exploring preferences for future treatment. Among 10 caregivers who had not heard of ACP, 5 proceeded to have further discussions after ACP counselling. ACP enhances caregivers' understanding of dementia and the persons with dementia, leading to initiation of conversations involving end-of-life care decisions that incorporate the patients' perspectives, planning for future care, and early involvement of other care providers (physicians and family members). Discussion: ACP in the mild stages of dementia promotes patient-centred care by enhancing caregiver's understanding and stimulating further conversations between patients and caregivers. Conclusion: Future research should focus on the congruency of decision-making on future healthcare preferences between patients and caregivers to further explore the utility of ACP in mild dementia.